NIR-emitting and photo-thermal active nanogold as mitochondria-specific probes. (10th March 2017) - Chakrabortty, Sabyasachi; Sison, Miguel; Wu, Yuzhou; Ladenburger, Anita; Pramanik, Goutam; Biskupek, Johannes; Extermann, Jerome; Kaiser, Ute; Lasser, Theo; Weil, Tanja
Abstract : We report a bioinspired multifunctional albumin derived polypeptide coating comprising grafted poly(ethylene oxide) chains, multiple copies of the HIV TAT derived peptide enabling cellular uptake as well as mitochondria targeting triphenyl-phosphonium (TPP) groups. Abstract : We report a bioinspired multifunctional albumin derived polypeptide coating comprising grafted poly(ethylene oxide) chains, multiple copies of the HIV TAT derived peptide enabling cellular uptake as well as mitochondria targeting triphenyl-phosphonium (TPP) groups. Exploring these polypeptide copolymers for passivating gold nanoparticles (Au NPs) yielded (i) NIR-emitting markers in confocal microscopy and (ii) photo-thermal active probes in optical coherence microscopy. We demonstrate the great potential of such multifunctional protein-derived biopolymer coatings for efficiently directing Au NP into cells and to subcellular targets to ultimately probe important cellular processes such as mitochondria dynamics and vitality inside living cells.